Addition of a bilateral access form of peripheral extracorporeal membrane oxygenation rescued a patient with idiopathic pulmonary arterial hypertension who developed circulatory collapse immediately after childbirth. (1st February 2020) - Adachi, Shiro; Shimokata, Shigetake; Yoshida, Masahiro; Imai, Ryo; Nakano, Yoshihisa; Okumura, Naoki; Suzuki, Susumu; Murohara, Toyoaki; Kondo, Takahisa
Abstract : Pregnancy is not advised for patients with Pulmonary hypertension (PH) because of high risk of PH crisis. However, some patients have undiagnosed idiopathic pulmonary arterial hypertension (IPAH) before pregnancy. Upfront combination therapy has high efficacy for patients with IPAH. However, some patients are unable to stand until upfront combination therapy has worked sufficiently. The extracorporeal membrane oxygenation (ECMO) system has been proposed as a bridging therapy to recovery for patients with IPAH. Here, we report a case where a novel form of peripheral ECMO assist plus upfront combination therapy containing intravenous epoprostenol rescued a female patient diagnosed with IPAH just after childbirth. Following this treatment, the patient could successfully transition from intravenous epoprostenol to oral selexipag.